Pengaruh Premi, Klaim, Dan Profitabilitas Terhadap Pertumbuhan Aset Pada Perusahaan Asuransi MAG Periode 2018-2021 - Arta Dewi, Dian; Yuniarta, Gede Adi (Universitas Pendidikan Ganesha, 2021)
This study aims to determine how and how much influence premiums, claims, and profitability on asset growth in MAG insurance companies. The variables studied include premiums, claims, and profitability as independent variables and asset growth as the dependent variable. This research belongs to the type of quantitative descriptive research. The population in this study is the MAG insurance company from 2018-2021, while the sample is 14 branch offices in Indonesia in 2018-2021. The data analysis technique used in this research is multiple linear regression analysis. Based on the results of statistical testing and discussion analysis, either simultaneously or partially premiums have no effect on asset growth. Claims, and profitability have a significant effect on asset growth. Keywords: Premiums, Claims, Profitability and Asset Growth